2018
DOI: 10.1152/ajpendo.00297.2018
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics approach reveals metabolic changes in the heart at birth

Abstract: During late gestation, the fetal heart primarily relies on glucose and lactate to support rapid growth and development. Although numerous studies describe changes in heart metabolism to utilize fatty acids preferentially a few weeks after birth, little is known about metabolic changes of the heart within the first day following birth. Therefore, we used the ovine model of pregnancy to investigate metabolic differences between the near-term fetal and the newborn heart. Heart tissue was collected for metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Following birth, the heart gradually transitions from utilizing lactate and glucose as primary energy substrates in utero to fatty acids, which is sustained in the healthy heart into adult life (2,32,33). Previous work in our laboratory has found that transcripts for BCAA degradation are enriched in fetal hearts in healthy sheep compared with newborn hearts on the first day of life (51). Additionally, studies in adult human hearts has suggested that BCAA degradation is diminished in the failing heart (27,48).…”
Section: Chronic Exposure To Excess Maternal Cortisol In Late Gestatimentioning
confidence: 92%
See 3 more Smart Citations
“…Following birth, the heart gradually transitions from utilizing lactate and glucose as primary energy substrates in utero to fatty acids, which is sustained in the healthy heart into adult life (2,32,33). Previous work in our laboratory has found that transcripts for BCAA degradation are enriched in fetal hearts in healthy sheep compared with newborn hearts on the first day of life (51). Additionally, studies in adult human hearts has suggested that BCAA degradation is diminished in the failing heart (27,48).…”
Section: Chronic Exposure To Excess Maternal Cortisol In Late Gestatimentioning
confidence: 92%
“…Nuclear magnetic resonance metabolomics analysis. HR-MAS proton nuclear magnetic resonance ( 1 H-NMR) was used to determine metabolites present in RV and LV free walls and intraventricular septum as previously described (51). Metabolites identified with this technique were not found to be significantly altered between different areas of the heart and were therefore treated as biological replicates, effectively defining cardiac tissue as our experimental unit (29) (Supplemental Table S1; Supplemental Material for this article is available online at the Journal website).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For metabolites with significant interaction effects between trimester and diabetes, a Tukey–Kramer post-hoc test was conducted to determine significant alterations over each trimester ( p < 0.05). Pathway analysis was conducted using Metaboanalyst with significant metabolites from each linear mixed-effects model as previously described [ 75 , 77 ]. Pathways not related to human metabolism or containing D-amino acids were removed from the results.…”
Section: Methodsmentioning
confidence: 99%